Complement-Mediated Thrombotic Microangiopathy and Spontaneous Splenic Rupture Associated With Cytomegalovirus Infection - Sadia Shabir MD; Caleb T Spencer MD; Arooj Tabassum MD; Arjun Chandra MD; Wasef Sayeh MD; Fadi Safi MD; Shahab Ud din MD (SAGE Publishing, 2023)
This is a case report of a previously healthy female patient with complement-mediated thrombotic microangiopathy (TMA) caused by a systemic cytomegalovirus infection that was successfully treated with plasmapheresis, steroids, and parenteral valganciclovir. Complement-mediated TMA is the result of various genetic mutations leading to complement abnormalities with overactivation of alternate complement pathway in response to a triggering infection. She also had splenic rupture without splenomegaly and was managed successfully without splenectomy.